Application of HPLC Coupled with a Charged Aerosol Detector to the Evaluation of Fructose, Glucose, Sucrose, and Inositol Levels in Fruit Juices, Energy Drinks, Sports Drinks, and Soft Drinks - Małgorzata Grembecka; Anna Lebiedzińska; Piotr Szefer (Beverages)
The study aimed to estimate the levels of fructose, glucose, sucrose, and inositol levels in sweetened beverages with a newly developed method using HPLC coupled with a charged aerosol detector (CAD). In total, 85 commercially available non-alcoholic beverages, including 18 energy drinks, 8 sports drinks, 15 soft drinks, 14 fruit drinks, 7 fruit nectars, and 22 fruit juices were analyzed by HPLC-CAD. The method was validated, and it was characterized by a wide concentration range (1–150 µg/mL), sensitivity, and good accuracy (94.9–103%). The results showed significant variation in fructose, glucose, and sucrose concentrations in energy drinks, sports drinks, soft drinks, fruit drinks, fruit nectars, and juice. The highest total sugar contents (fructose, glucose, sucrose, and inositol) were found in energy drinks (14.2 g/100 mL), followed by fruit nectars (13.7 g/100 mL) and soft drinks (12.7 g/100 mL). Statistical analysis (Spearman correlation test, Kruskal–Wallis test) of the data showed significant relationships between particular sugars in the analyzed products.